Effect of HCl Concentration and Acetone Washing on the Dielectric and Conduction Properties of Polyaniline Salts - Mohanty, Jayashree; Mishra, S.R.; Badapanda, Tanmaya; Anwar, S. (Recent Innovations in Chemical Engineering, 2021)
Background: In order to know the effect of acid concentration, comparative electrical properties of PANI salt samples prepared in two different media like water, 1M HCl and 2M HCl, have been studied. Methods: To know the effect of acetone washing on the electrical behavior of the polymer, the polymer samples were washed with acetone. The X-ray diffraction pattern shows a crystalline nature of all the prepared PANI salt samples except non-acetone washed PANI salt prepared in 2M HCl. The SEM micrograph suggests a uniform and continuous morphology for PANI salts prepared in 1M HCl, agglomerated granulated structure for PANI salts prepared in 1M HCL, and fiber type structure for PANI salts prepared in 2M HCl. Results: The study showed that the dielectric constant decreases with frequency in the case of all the synthesized polymer samples. The variation of AC conductivity of the synthesized polymer samples with respect to the frequency at room temperature follows the power law. Through the fitting parameters, the DC conductivity was found. Conclusion: The results showed that the polymer sample, which was prepared in water medium and not washed with acetone, had the highest dielectric and conductivity values, whereas for acetone washed samples highest dielectric and electrical conductivity was observed for the sample prepared in 2M HCl.
Keywords: dielectric properties